The educational efforts of Sultan Muhammad Al-Fateh and its role in enhancing the scientific aspect of the Islamic civilization in the Ottoman era - Husawi, Manahel Suliman (Journal of Educational and Psychological Sciences, 2019)
This study aimed at uncovering the educational efforts of Sultan Mohammed Al-Fatih and its role in enhancing the scientific aspect of the Islamic civilization in the Ottoman era by identifying the most important features of the personality of Sultan Mohammed Al-Fatih, the influence of societal factors in the era of Sultan Mohamed Al-Fatih, Mohammed Al-Fatih and its role in strengthening the scientific aspect of the Islamic civilization in the Ottoman era, and to clarify the ways to benefit from them at the present time. To achieve study’s goals, the researcher used the historical approach. The results of the research show: The political and security stability in the Ottoman Empire supports cultural development and stimulates the scientific and cultural conditions of production and creativity in educational and scientific institutions. Also, the cultural coexistence with the other created a fusion of the ancient civilizations that existed in Constantinople before the conquest. In the light of the results, the study recommended the following: establishing research center for Ottoman studies and all the manuscripts and documents in the Saudi universities for easy access to researchers. Besides, establishing a scientific center for the translation of modern and old Turkish language in Saudi universities.